2021
DOI: 10.3389/fcimb.2021.657245
|View full text |Cite
|
Sign up to set email alerts
|

The Human Bone Marrow Is Host to the DNAs of Several Viruses

Abstract: The long-term impact of viruses residing in the human bone marrow (BM) remains unexplored. However, chronic inflammatory processes driven by single or multiple viruses could significantly alter hematopoiesis and immune function. We performed a systematic analysis of the DNAs of 38 viruses in the BM. We detected, by quantitative PCRs and next-generation sequencing, viral DNA in 88.9% of the samples, up to five viruses in one individual. Included were, among others, several herpesviruses, hepatitis B virus, Merk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…The authors found that the MSCs derived from healthy donors contained viral DNA of parvovirus B19. Viral DNA has also been found in human bone marrow ( 43 ). The most common were B19V and torque teno virus (TTV): 62.9%, Epstein-Barr virus (EBV): 14.8%, Merkel cell polyomavirus (MCPyV): 11.1%, and human herpesvirus 7 (HHV-7): 7.4%.…”
Section: Viral and Mycoplasma Containment In Mscsmentioning
confidence: 99%
“…The authors found that the MSCs derived from healthy donors contained viral DNA of parvovirus B19. Viral DNA has also been found in human bone marrow ( 43 ). The most common were B19V and torque teno virus (TTV): 62.9%, Epstein-Barr virus (EBV): 14.8%, Merkel cell polyomavirus (MCPyV): 11.1%, and human herpesvirus 7 (HHV-7): 7.4%.…”
Section: Viral and Mycoplasma Containment In Mscsmentioning
confidence: 99%
“…HBV DNA can be found in the liver beyond serological resolution of chronic infection (termed occult HBV infection, OBI)[87,88], however, HBV persistence in other organs during OBI has been limitedly described. Evidence of extra-hepatic HBV DNA also exists in ancient and modern bones [36,89] and in bone marrow [43]. Together these ndings call for further assessment of the infectivity of all organs from chronic HBV carriers in transplantation medicine [88,90].…”
Section: Discussionmentioning
confidence: 99%
“…The baits were 100 nucleotides long, designed with 2X tiling, and targeted the full-length sequences of 38 human DNA viruses (parvovirus B19; torque teno virus; nine herpesviruses; polyomaviruses 1-13; hepatitis B virus; papillomavirus types 2, 6, 11, 16, 18, 21, 45; bocaviruses 1-4; cutavirus; simian virus 40; and variola viruses minor and major), as described [36,43].…”
Section: Viral Enrichment and Deep Sequencingmentioning
confidence: 99%
“…The baits were 100 nucleotides long, designed with 2X tiling, and targeted the full-length sequences of 38 human DNA viruses (parvovirus B19; torque teno virus; nine herpesviruses; polyomaviruses 1-13; hepatitis B virus; papillomavirus types 2, 6, 11, 16, 18, 21, 45; bocaviruses 1-4; cutavirus; simian virus 40; and variola viruses minor and major), as described 36,37 .…”
Section: Viral Enrichment and Deep Sequencingmentioning
confidence: 99%